2018
DOI: 10.25103/jestr.112.22
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Mechanisms in Dual-Phase Steel: Influence of Martensite Volume Fraction and Ferrite Grain Size

Abstract: The influence of Martensite Volume Fraction (MVF) on fracture mechanisms in a Dual Phase steel with two different grain sizes was studied in this work. Ferrite-Martensite microstructure was obtained by an intercritical heat treatment for both groups of grain sizes. The results show a direct relationship between a higher temperature during the intercritical heat treatment and the increase of the MVF. The fine microstructure with higher MVF presents a high tensile strength and a good ductility. Furthermore, in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…[21,22] Pakzaman et al stated that microstructure volume fraction, phase distribution, and morphology limit the deformation process and the stress partitioning. [23] Furthermore, the authors of the current study have previously documented that increasing the amount of martensite in the ferrite matrix increases the dual-phase steel mechanical response under dynamic impact conditions [24] and fatigue. [25] Due to the intercritical heat treatment temperature range used in the dual-phase steel production, the diffusion mechanism is less effective in transporting interstitial carbon atoms, so the resulting martensite produced during the quenching process has lower yield stress and hardness because of the lower and heterogeneous distribution of carbon content.…”
mentioning
confidence: 51%
“…[21,22] Pakzaman et al stated that microstructure volume fraction, phase distribution, and morphology limit the deformation process and the stress partitioning. [23] Furthermore, the authors of the current study have previously documented that increasing the amount of martensite in the ferrite matrix increases the dual-phase steel mechanical response under dynamic impact conditions [24] and fatigue. [25] Due to the intercritical heat treatment temperature range used in the dual-phase steel production, the diffusion mechanism is less effective in transporting interstitial carbon atoms, so the resulting martensite produced during the quenching process has lower yield stress and hardness because of the lower and heterogeneous distribution of carbon content.…”
mentioning
confidence: 51%
“…Another key microstructure feature of the ferritic-pearlitic steel was the initial ferritic grain size. There have been many studies on the effects of d f on mechanical properties of ferritic-pearlitic [65-69] and resultant DP steels [70-72]. For instance, Karmakar et al [73] reported that grain refinement in DP steels led to enhancements of both strength and ductility.…”
Section: Prior To Intercritical Annealingmentioning
confidence: 99%